2015
DOI: 10.1093/molbev/msu405
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution and Functional Impact of Human Deletion Variants Shared with Archaic Hominin Genomes

Abstract: Allele sharing between modern and archaic hominin genomes has been variously interpreted to have originated from ancestral genetic structure or through non-African introgression from archaic hominins. However, evolution of polymorphic human deletions that are shared with archaic hominin genomes has yet to be studied. We identified 427 polymorphic human deletions that are shared with archaic hominin genomes, approximately 87% of which originated before the Human–Neandertal divergence (ancient) and only approxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 45 publications
2
53
0
Order By: Relevance
“…One study has highlighted DMBT1 to be a strong candidate for ancient balancing selection in the genome (49). Another recent study has identified the region upstream of DMBT1 to show unusually negative Tajima's D (in the fifth percentile genome wide) in Europeans, supporting our model of selection (50). However, the effect on SNP diversity of a rapidly mutating CNV undergoing fluctuating geographically structured selection remains unclear.…”
Section: Discussionmentioning
confidence: 52%
“…One study has highlighted DMBT1 to be a strong candidate for ancient balancing selection in the genome (49). Another recent study has identified the region upstream of DMBT1 to show unusually negative Tajima's D (in the fifth percentile genome wide) in Europeans, supporting our model of selection (50). However, the effect on SNP diversity of a rapidly mutating CNV undergoing fluctuating geographically structured selection remains unclear.…”
Section: Discussionmentioning
confidence: 52%
“…This ~32kb deletion variant overlaps 2 genes, LCE3B and LCE3C , which are both involved in skin tissue repair. We recently showed that this deletion variant is derived in the Homo lineage and that the deletion is present in the Denisovan genome, but absent in the Neanderthal genome [13]. In the same study, we were able to rule out archaic introgression and concluded that incomplete lineage sorting best explains the observed allele sharing at this locus.…”
Section: Introductionmentioning
confidence: 72%
“…The green boxes represent π and Tajima’s D scores calculated for the size-matched downstream regions of non-exonic ancient deletions. These deletions are comparable to the LCE3BC deletion in the sense that they were also found to have evolved before Human Neanderthal/Denisovan divergence and that they are similarly high in allele frequency [58]. P -values (Wilcoxon Test) are shown on top of the comparisons …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…a higher rate of genetic drift [5]. This suggests that weakly deleterious exonic alleles may have been effectively neutral and drifted up in frequency in Neanderthals [2830], only to be slowly selected against after introgressing into modern human populations of larger effective size. To test this hypothesis, we simulated a simple model of a population split between AMH and Neanderthals, using a range of plausible Neanderthal population sizes after the split.…”
Section: Resultsmentioning
confidence: 99%